EVALUATION OF THE EFFECT OF TRASTUZUMAB AND NON-TRASTUZUMAB THERAPY ON OVERALL SURVIVAL AND PROGNOSIS OF HER2-POSITIVE BREAST CANCER at FATMAWATI HOSPITAL JAKARTA 2019-2024. - Elis - (RSUP Fatmawati, 2026)
Cancer is one of the leading causes of death worldwide, with breast cancer being the most common type. According to GLOBOCAN 2022, there were 178,393 breast cancer cases globally, including 66,271 (16.2%) in Indonesia. The HER2-positive subtype is more aggressive and associated with a poorer prognosis. This study aimed to evaluate the effect of trastuzumab and non-trastuzumab therapies on overall survival (OS), identify clinical factors influencing therapeutic outcomes, and assess their impact on prognosis among HER2-positive breast cancer patients at Fatmawati Central General Hospital, Jakarta, during 2019–2024. A retrospective cohort design was applied using secondary data from medical records. Data were analyzed using the Kaplan–Meier method, log-rank test, and Cox proportional hazards model. Among 178 patients, 31 (17.4%) experienced an event, and 147 (82.6%) were censored. Trastuzumab, particularly combined with hormonal therapy, showed the best survival outcome (mean OS 1,096 days) with no events, while the non-targeted group had the highest mortality (55%) with a mean OS of 855 days (p = 0.13). Tumor size (p = 0.02) and metastatic site (p = 0.04) significantly affected survival. The low-risk group, mostly receiving trastuzumab, had the best prognosis (4.4% events), whereas the high-risk group showed poorer outcomes (40% events; log-rank p < 0.0001; C-index = 0.820). Keywords: breast cancer, HER2-positive, trastuzumab, targeted therapy, overall survival, Cox regression